Penerapan Model Pembelajaran Inkuiri Terbimbing Terhadap Hasil Belajar Siswa Di SMA Negeri 1 Airmadidi Pada Materi Sifat Koligatif Larutan - Ilham Mahmud; Sonny Lumingkewas; Joice Caroles (Chemistry Department, Universitas Negeri Manado, 2019)
This research is experimental design was posttest only control group design. Determination of the sample using techniques random sampling and obtained two classes with the number of each class of 33 students. Experimental class 3 XII IPA and 4 XII IPA control class. The research was conducted to find out the result data inquiry learning model on the material colligative solution on the results of class XII student IPA at SMA Negeri 1 Airmadidi. The purpose of this study was to see increase learning outcomes students using inquiry model learning on the material colligative solution. Results of the study were analyzed to test the hypothesis (t test) at α = 0.05 was obtained tcount> ttable ie 3.15 > 1.66 means H1 received and there is a real increase, the result of learning to use inquiry learning model. As well as describing the average ratio of student learning outcomes using the experimental class higher inquiry learning model 80.00, compared with the control class that uses the conventional learning model that is 68.18.